Professional learning communities to facilitate professional development for using digital technology in the classroom: a teacher-based program evaluation - Lomos, Catalina; Schaap, Harmen; Luyten, J. W. (Hans); Kesting, Frauke; Lima da Cunha, Filipe; Frieseisen, Carole; Telli, Sibel; Fowler, Sam (Frontiers in Education, 2025)
This article presents a shift from traditional “technical” professional development (PD) to a PD of “praxis” and reflects on the benefits and barriers that this entails. Often, PD in digital technology is unsustainable because it provides simple tips or a few sample lessons that teachers are happy to deliver until the technology fails or becomes obsolete. PD in which teachers are actively engaged in exploring their own practice and understanding the rationale behind the implementation of technology is more likely to result in teachers who can adapt current technologies and reflect on the constraints they inherently present. Professional learning communities (PLCs), as a long-term support for PD, allow this to happen within the context of the school and its specific affordances. This article describes one such innovative PD program designed and developed by a team of one researcher and three teachers and implemented with 51 teachers from 10 primary schools in Luxembourg. The primary goal of the PD program was to support teachers in using a digital learning platform for mathematics in their classrooms. The secondary goal was to facilitate the emergence of PLCs within their schools, so that teachers could support each other in the long term. The format of the program was with and about technology, as it was also delivered online, with teachers meeting face-to-face and working together in their schools. The collaborative nature of the program—the fact that teachers had to set common goals for the training, design and plan collaborative activities, and reflect on how best to integrate the digital learning platform into their classroom practice—was the greatest benefit reported by teachers in all groups, and it increased over the six consecutive training sessions. Most teachers reported that the frequency of their use of the digital learning platform in the classroom increased and strongly increased as a result of the training. New designs for teacher PD with and about digital technologies can build on theories of effective teacher professional learning through PLCs and provide teachers with a safe and sustainable environment in their school for further practice and development.